PEACEFUL DIPLOMACY IN THE SOUTH CHINA SEA: SETTLEMENT OF INTERNATIONAL DISPUTES THROUGH ARBITRATION AND NEGOTIATION - Perjalanan, Tahta (Fakultas Hukum Universitas Djuanda, 2024)
The South China Sea dispute is one of the hottest conflicts in regional politics, involving a number of countries in the Asia-Pacific region. The complexity of this dispute is rooted in overlapping territorial claims, competition for rich natural resources, and historical tensions between the countries involved. This study aims to discuss the resolution of international disputes through peaceful diplomacy, with a case study focusing on the South China Sea Dispute. The controversy over territorial and resource claims in the region culminated in an arbitration court, which resulted in a decision in favor of the Philippines. However, the resolution of the dispute did not stop there; this article reviews the development of post-arbitration diplomacy between China and the Philippines, culminating in a joint agreement to develop and manage resources in the South China Sea. The results of the study show that the role of the arbitration court, government response, and negotiation dynamics support peaceful resolution. The conclusion highlights global implications and provides valuable lessons for dealing with international disputes, emphasizing that diplomacy remains a key pillar in building and maintaining relations between countries.